POTENSI TRANSMISI VIRUS AVIAN INFLUENZA DARI BABI DAN UNGGAS PADA PETERNAKAN BABI DI WILAYAH TANGERANG, PROVINSI BANTEN - NLP Indi Dharmayanti; Atik Ratnawati (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Pigs have an important role in the ecology of influenza virus since they are sensitive to influenza viruses from human and avian origin. Influenza A virus has a host specificity, although not absolute, so most of the AI virus circulating in various species is only limited to the species, but sometimes there are interactions between different AI virus species or strain. Farming systems that combine a variety of animal species together in the same or around the sites have an important role in the spread of disease and transmission between species. This study is aimed to investigate the cycle of AI virus in order to determine the potential occurrence of viral transmission among species pig and bird at the pig farm that also raising poultry. Influenza virus was identified by methods of RT-PCR and qRT-PCR. The results showed that the novel H1N1 pandemic virus was detected in one pig farm in Tangerang (Banten Province). The AI/H5 virus is also detected in the pig farm that also raises poultry or poultry/pig farmers and located adjacent each other. The AI virus / influence A is also detected in most of the pigs. Detection of AI viruses that infected in pig farm which kept birds or poultry farm around the pigs farm had potential of AI virus transmission from birds species to pig or vise versa. The pigs could serve as a mixing vessel, thus providing opportunities likelihood of reassortant viruses.